A Permian (late Guadalupian) brachiopod fauna from northeast Mexico and their paleobiogeographic affinities. (June 2019) - Torres-Martínez, Miguel A.; Heredia-Jiménez, Daniela P.; Quiroz-Barroso, Sara A.; Navas-Parejo, Pilar; Sour-Tovar, Francisco; Quiroz-Barragán, Jesús
Abstract: In this work, we report a brachiopod fauna composed of 30 species within 25 genera, belonging to the orders Productida, Orthotetida, Orthida, Rhynchonellida, Athyridida, Spiriferida, Spiriferinida and Terebratulida from the Capitanian (late Guadalupian) of Las Delicias, Coahuila, Mexico. The genera Probolionia, Anemonaria, Waagenoconcha, Grandaurispina, Edriosteges, Ramavectus, Enteletes and Thedusia, in addition to the species Linoproductus nasutus, Rhynchopora guadalupensis, Wellerella girtyi, Composita parasulcata, Composita prospera, Hustedia bipartita, Hustedia opsia, Hustedia stataria, Martinia rhomboidalis and Spiriferella sulcifer are reported for the first time in Mexico. Marginifera minor and Liosotella subquadrata are taxonomically reviewed and renamed. The finding of 15 species commonly recorded in the late Guadalupian, together with the presence of the ammonoid Timorites, corroborates the Capitanian age for the Las Manuelas I section. Thus, the stratigraphic location of the studied section allowed delimiting the age of the upper levels of La Difunta unit to the late Guadalupian. The occurrence of 13 species that had only been described in localities of Texas confirms that during Capitanian the brachiopod fauna studied was related to the biotic Grandian Province. Then again, taxa that had a wide distribution in the Guadalupian were recorded, such as Bathymyonia nevadensis, Enteletes wordensis, Linoproductus nasutus, Hustedia stataria and Martinia rhomboidalis from the United States and China, Japan, Turkey or Russia. This exchange of marine biota among Permian provinces has been associated with a marine connection located about the middle of the Panthalassa Ocean. Due to the proximity of Las Delicias and Texas, both regions could had been influenced by the same paleoequatorial current, suggesting that North American brachiopods found in Paleotethys provinces could also had come from Mexico. Highlights: 30 species of brachiopods from the Capitanian (middle Permian) of Mexico are recorded. Two taxa are taxonomically reviewed and renamed. 18 taxa are reported for first time in Mexico. The taxa studied are related to Permian fauna of the biotic Grandian Province. Some species support the idea of a marine connection between west Pangea and Paleothetys.